การใช้วัฏจักรการเรียนรู้ 7 ขั้น ร่วมกับการเกษตรอินทรีย์เพื่อพัฒนาผลสัมฤทธิ์ทางการเรียนและทักษะกระบวนการทางวิทยาศาสตร์เรื่องระบบนิเวศ และเจตคติต่อการอนุรักษ์สิ่งแวดล้อมของนักเรียนชั้นมัธยมศึกษาปีที่ 3 - Chaiteka, Sukanda; Kesonbua, Wirot (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2014)
Using the 7-E’s Learning Cycle Integrated with Organic Farming to Develop Students’ Achievement and Science Process Skill in Ecosystem Unit, and Attitudes toward Environmental Conservation for Grade 9 Students Sukanda Chaiteka and Wirot Kesonbua รับบทความ: 14 มีนาคม 2555; ยอมรับตีพิมพ์: 22 เมษายน 2555 บทคัดย่อ การใช้วัฏจักรการเรียนรู้ 7 ขั้น ร่วมกับการเกษตรอินทรีย์ เพื่อพัฒนาผลสัมฤทธิ์ทางการเรียนและทักษะกระบวนการทางวิทยาศาสตร์เรื่องระบบนิเวศ และเจตคติต่อการอนุรักษ์สิ่งแวดล้อมของนักเรียนชั้นมัธยมศึกษาปีที่ 3 โรงเรียนนาน้อย จังหวัดน่าน ภาคเรียนที่ 1 ประจำปีการศึกษา 2554 จำนวน 39 คน วัตถุประสงค์ของการวิจัยเพื่อ 1) พัฒนาผลสัมฤทธิ์ทางการเรียนวิชาวิทยา-ศาสตร์ 2) ศึกษาทักษะกระบวนการทางวิทยาศาสตร์ และ 3) ศึกษาเจตคติต่อการอนุรักษ์สิ่งแวดล้อม ดำเนินการวิจัยโดย 1) วัดผลสัมฤทธิ์ทางการเรียนก่อนเรียน 2) ดำเนินกิจกรรมการเรียนรู้และประเมินทักษะกระบวนการทางวิทยาศาสตร์ และ 3) วัดผลสัมฤทธิ์ทางการเรียนและเจตคติต่อการอนุรักษ์สิ่งแวดล้อมหลังเรียน ผลการวิจัยพบว่า 1) นักเรียนมีผลสัมฤทธิ์ทางการเรียนเฉลี่ยคิดเป็นร้อยละ 76.75 ซึ่งสูงกว่าเกณฑ์ที่กำหนดไว้ (70%) และมีจำนวนนักเรียนผ่านเกณฑ์ร้อยละ 76.92 ซึ่งสูงกว่าเกณฑ์ที่กำหนดไว้ (70%) 2) นักเรียนมีทักษะกระบวนการทางวิทยาศาสตร์เฉลี่ยเท่ากับร้อยละ 81.25 ซึ่งสูงกว่าเกณฑ์ที่กำหนดไว้ (70%) และมีจำนวนนักเรียนร้อยละ 100 ได้คะแนนสูงกว่าเกณฑ์ที่กำหนดไว้ (70%) และ 3) นักเรียนมีเจตคติต่อการอนุรักษ์สิ่งแวดล้อมอยู่ในระดับดี โดยมีค่าเฉลี่ยเท่ากับ 3.95 คำสำคัญ: วัฏจักรการเรียนรู้แบบ 7 ขั้น เกษตรอินทรีย์ ผลสัมฤทธิ์ทางการเรียน ทักษะกระบวนการทางวิทยาศาสตร์ เจตคติต่อการอนุรักษ์สิ่งแวดล้อม Abstract The 7-E’s learning cycle integrated with organic farming for developing science process skill and students’ achievement in the topic of ecosystem, and attitudes toward environmental conservation was to investigate 39 Grade 9 students from Nanoi School, Nan province, during the first semester of academic year 2011. The purpose of the present research included: 1) developing students’ achievement in science, 2) investigation of science process skill, and 3) studying the students’ attitude toward environmental conservation. Research was operated by 1) measuring students’ achievement before learning, 2) performing learning activities and evaluating science process skill, and 3) measuring students’ achievement and attitude toward the environmental conservation after learning. The results indicated that 1) the post achievement score of students was 76.75%, which was higher than minimum criterion (70%), and 30 students or 76.92% of the group was passing, which are also higher than minimum criterion (70%), 2) students’ score in science process skill are 81.25 %, which are higher than minimum criterion (70%), and 39 students or 100% of the group are passing, which are also higher than minimum criterion (70%), and 3) student demonstrated a good level in attitudes toward the environmental conservation, with 3.95 levels by means. Keywords: The 7-e’s learning cycle, Organic farming, Learning achievement, Science process skill, Attitudes toward environmental conservation